PENGUKURAN KUALITAS HIDUP PASIEN HEMODIALISIS GAGAL GINJAL KRONIK DI RSUD ULIN BANJARMASIN MENGGUNAKAN INSTRUMEN EQ5D - Saftia Aryzki; Maudy Namirah Raudatullis Wanda; Yugo Susanto; Mochammad Maulidie Alfiannor Saputera; Aditya Maulana Perdana Putra; Karani Karani (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Chronic renal failure is a progressive and irreversible renal function disorder in which the body's ability to fail to maintain metabolism, fluid and electrolyte balance. Chronic kidney failure can interfere with the quality of life of patients, it is necessary to measure the quality of life of patients with chronic renal failure. Measuring the quality of life of patients with chronic renal failure using the Indonesian version of the EQ5D questionnaire. The purpose of this study was to determine the quality of life of chronic renal failure hemodialysis patients in RSUD Ulin Banjarmasin using the EQ5D instrument. This study is an observational study conducted prospectively. Data was collected by filling out the EQ5D questionnaire by all patients with chronic renal failure. The population of this study were chronic renal failure patients who underwent hemodialysis in Hemodialysis Outpatient Services at Ulin Banjarmasin Hospital in June-July 2018 as many as 360 patients and a sample of 207 patients who met the inclusion and exclusion criteria using non random sampling / non-probability sampling techniques accidental sampling. Based on the research that has been done in the Hemodialysis Outpatient Hospital Ulin Banjarmasin, it was found that the average quality of life was 0.792, with a quality of life ≥ 0.792 of 69 patients (33.33%) in the category of good quality of life and quality of life ≤ 0.792 138 patients (66.66%) in the poor quality of life category.